Research trends in multimodal metaphor: a bibliometric analysis - Zhong, Zenan; Wen, Suijun; Chen, Shukun (Frontiers in Psychology, 2023)
The concept of multimodal metaphor has generated a growing body of literature over the past decades. However, a systemic review of the domain seems to be lacking in relevant literature. This study, therefore, is an attempt to conduct a bibliometric analysis of the field of multimodal metaphor during 1977–2022, with a focus on 397 relevant publications retrieved from the Web of Science Core Collection (WoSCC) with the visualization tool VOSviewer. Some major quantitative findings are: (i) the number of publications in multimodal research began to surge in 2010 upon the seminal work of Forceville’s (2009); (ii) USA, China and Spain are the most productive countries; (iii) journals in the field of advertising, communication and linguistics are important sources of publications; and (iv) eleven clusters of keywords are identified, such as “visual metaphor”, “persuasion”, “pictures”, “impact”, “multimodal metaphor”, “model”, etc., representing crucial areas of interests. We also identified, by qualitative observations, three research trends in multimodal metaphor, driven by cognitive linguistic theory, the theory of pragmatics and visual/multimodal rhetoric theory, respectively. Various theoretical perspectives may shed light on possible further research on multimodal metaphor.